Determinación de los niveles de insulina y glucosa como indicadores de la eficiencia reproductiva y productiva, en vacas puerperales de la Hoya de Loja - Rosales Sánchez, Cristian Eduardo (2014)
In milky ranching from the Loja wide valley, productive and reproductive efficiency rates are affected by inadequate management in health, management, food and nutrition, this as a determinant of the expression of reproductive efficiency. Mismatches and nutritional errors will manifest themselves in the breeding and milk production. The concentrations of indicators metabolic glucose and insulin in the productive and reproductive efficiency have not been studied to assess and analyze the relationship that may exist between the animals subjected under managed conditions. For the determination of glucose and insulin levels as indicators of the productive and reproductive efficiency in postpartum cows, These were collected in test tubes sterile and conserved in a cooler with an approximate temperature at 4° C until further analysis in a veterinary diagnostic laboratory, post-partum estrus presentation data collection, delivery design, body condition and dairy production, were recorded daily. Glucose was made as soon as possible using the method without Deproteinization, While for insulin, blood serum was stored at previously identified cryovials, These were kept at - 20 ° C for 30 days, fulfilled this time were thawed for analysis by ELISA (Kit Accubind, Monobind Inc.). General average glucose concentrations were 47,90, 47,09 y 46,43 mg/dl in 15, 30 and 45 days post-partum, respectively; While insulin was variable with 5,54, 5,05 y 5,28 uU/ml in the studied postpartum days, as to body condition and milk production increased after the postpartum, The cows were grouped according to the presentation of postpartum estrus and labor conception in three periods, between 46 to 90 days postpartum the Glycemic levels were 51,38 mg/dl Postpartum Estrus cows, and 50,61 mg/dl on cows with labor conception, Meanwhile, cows with both intervals in the first 45 days, and greater than 90 days postpartum blood glucose was 46,00 mg/dl for which exhibited postpartum estrus and 47,30 mg/dl cows labor-conception in 45 days postpartum and 45,71 and 45,64 mg/d for cows older than 90 days. The levels of insulin in the period between 46 to 90 days postpartum cows had 3,37 y 3,52 uU/ml for the variable delivery estraus and labor-conception, respectively. To greater body condition, the greater milk production. High levels of glucose and low concentrations of insulin are characteristic of the interval labor –conception (IPCC) among the 46 to 90 days.